Optimal Multi Load Shedding for Voltage Security Control in Bulk Power System - Abd Shukor S.F.; Musirin I.; Hamid Z.A.; Mansor M.H.; Sentilkumar A.V.; Abd Samat A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer programming; Electric power plant loads; Electric power system control; Electric power system security; Optimization; Stability; Load-shedding; Maximum permissible load; Optimization techniques; Power; Security controls; Stability indices; Under-voltage load shedding; Voltage collapse; Voltage security; Voltage stability analysis; Electric load shedding